2013 and 2014 National Science Foundation Political Science Program Awards. (PS: Political Science & Politics, 2015)
The article presents the recipients of the National Science Foundation 2013-2014 Political Science Program Awards in the U.S. It states that the program funds eight regular awards, 14 doctoral dissertation improvement awards, and Grant for Rapid Response Research (RAPID). The recipients include Stewart Charles of the Massachusetts Institute of Technology, Sunshine Hillygus of Duke University, and Paul Sniderman of Stanford University.